Hydropower and its development - Janusz Steller (Acta Energetica, 2013)
Even if the documented history of hydropower reaches back as far as 5000 years ago, it owes its rapid acceleration in growth to the industrial revolution at the beginning of the nineteenth century. The end of the twentieth century brought about new challenges associated, on the one hand, with a growing demand for ancillary grid services, and on the other with new requirements for mitigating the environmental impact. Hydropower technology expansion had come about in a manner aiming to at least partially exploit the mechanical energy of sea and ocean waters. This study points out to the most important trends in and barriers to hydropower development, with particular focus on the situation in Poland. This author sees the main threats to Polish hydropower development in how it is perceived solely through the prism of the generation of a particular volume of green energy, and a total underestimation of the quality of electricity supply and the numerous non-energy benefits resulting from hydroelectric power plant operation.